Pengaruh Efisiensi Biaya Operasional (BOPO) dan Non-Performing Loan (NPL) terhadap Profitabilitas Bank Digital yang Terdaftar di BEI Periode 2020-2024 - Jovita Shafa Purwanti; M. Hamid Bishri (AKUNTANSI 45, 2026)
This study aims to determine the extent to which BOPO and NPL partially and simultaneously influence profitability. The independent variables in this study are Operational Cost Efficiency as measured by the ratio of Operating Costs to Operating Income (BOPO) and Non-Performing Loans as measured by Non-Performing Loans (NPL). While the dependent variable used in this study is Profitability as measured by Return on Assets (ROA). The population in this study was 17 banking companies listed on the Indonesia Stock Exchange in 2020-2024. The sample of this study used a purposive sampling method to obtain 6 banking sector companies that met the criteria. The results of this study indicate that BOPO partially has a significant effect on profitability with a significance value of 0.00>0.05 and NPL does not significantly affect profitability with a significance value of 0.086<0.05. Simultaneously, BOPO and NPL have a significant effect on profitability with a significance value of 0.00<0.05.